Experiências docentes projetos formativos no Pibid e Residência Pedagógica - Schäffer, Ana Maria de Moura (Editora Oficina Universitária, 2023)
Government programs for teacher training and Pedagogical Residency emerge in the Brazilian educational scenario as initiatives that highlight practical spaces in real teaching contexts, as they promote the exchange of experiences and the academic growth of students and teachers. This is what this work is about, by presenting readers with actions that shed light on educational relationships. Thus, the experiences narrated in the book make up material that encourages cooperation, participation, academic research and the democratization of the school space.